2018
DOI: 10.1021/acs.chemmater.7b03472
|View full text |Cite
|
Sign up to set email alerts
|

Clickable Multifunctional Large-Pore Mesoporous Silica Nanoparticles as Nanocarriers

Abstract: Large-pore mesoporous silica nanoparticles (LP-MSNs) with defined particle size (<200 nm) are promising carrier systems for the cellular delivery of macromolecules. Ideal nanocarriers should be adaptable in their surface properties to optimize host−guest interactions; thus, surface functionalization of the nanovehicles is highly desirable. In this study, we synthesized various monofunctional LP-MSNs by incorporating different organic groups into the silica framework via a co-condensation approach. Further, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Also, MSNPs can be PEGylated on the outer surface via a mercapto-reactive maleimide-PEG linker. In this case, the inner surface of the MSNPs was modified with aza-dibenzocy-clooctyne derivatives to enable copper-free “click” chemistry reactions for the conjugation of azide-terminated cargos [ 109 ]. Another example is the PEGylation of AuNPs via grafting-to approach, which can be performed using thiolated PEG molecules [ 110 ].…”
Section: Core-brush Nanoparticlesmentioning
confidence: 99%
“…Also, MSNPs can be PEGylated on the outer surface via a mercapto-reactive maleimide-PEG linker. In this case, the inner surface of the MSNPs was modified with aza-dibenzocy-clooctyne derivatives to enable copper-free “click” chemistry reactions for the conjugation of azide-terminated cargos [ 109 ]. Another example is the PEGylation of AuNPs via grafting-to approach, which can be performed using thiolated PEG molecules [ 110 ].…”
Section: Core-brush Nanoparticlesmentioning
confidence: 99%
“…This design resulted into a high ionic rectification and ion gating via pH‐responsive groups. Bein and co‐workers [ 34 ] reported multifunctional mesoporous silica nanoparticles to create a drug delivery system with controlled cargo release by using redox‐ or pH‐sensitive groups. Although first examples of local functionalization of pores as well as multifunctionalization of surfaces are described, typically both concepts are not combined and local placement of different functional units inside one pore has not been accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…Ordered MSNs are often synthesized using TEOS (tetraetoxysilane) as a silica source and ionic (for e.g., MCM-41 systems) or non-ionic (for SBA-15 systems) surfactants governing inorganic-organic mesophase formation [6]. It has been reported that the size and shape of MSNs can be easily tailored by varying the temperature [7,8], reactants ratio [9], pH [10], surfactant chain length [11], as well as the addition of functional organosilanes [12]. Properly tailored MSNs found applications in numerous fields such as drug delivery systems [13,14], wastewater treatment [15,16], catalysis [17,18], fabrication of nanoreactors [19,20] and nanocontainers [21,22].…”
Section: Introductionmentioning
confidence: 99%